Shorter sperm telomere length in association with exposure to polycyclic aromatic hydrocarbons: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments. (October 2016) - Ling, Xi; Zhang, Guowei; Chen, Qing; Yang, Huan; Sun, Lei; Zhou, Niya; Wang, Zhi; Zou, Peng; Wang, Xiaogang; Cui, Zhihong; Liu, Jinyi; Ao, Lin; et al.
Abstract: It has been well demonstrated that polycyclic aromatic hydrocarbons (PAHs) can cause reproductive toxicity, and shorter telomere length in sperm may be one of the factors causing male infertility. However, whether exposure to PAHs is associated with sperm telomere length (STL) has never been evaluated. The present study aimed to assess the potential association between PAHs exposure and STL, and to explore potential biomarkers that may predict the effects of low-level exposure to PAHs on human sperm. Questionnaires and biological samples were collected from 666 volunteers participating in the Male Reproductive Health in Chongqing College Students (MARHCS) cohort study in 2014. Semen parameters were measured for 656 participants, while urinary PAH metabolites, STL and sperm apoptosis were successfully measured for 492, 444 and 628 participants, respectively. The linear regression analysis revealed that increased levels of urinary 1-hydroxypyrene (1-OHPyr) and 1-hydroxynapthalene (1-OHNap) were associated with decreased STL (− 0.385; 95% CI, − 0.749, − 0.021 for 1-OHPyr; and − 0.079; 95% CI, − 0.146, − 0.011 for 1-OHNap). The significant negative associations remained after adjusting for potential confounders. However, no significant associations were observed between urinary PAH metabolites and semen quality or sperm apoptosis. We also administrated rats with benzo[ a ]pyrene (B[ a ]P; 0, 1, 5, and 10 mg/kg) for 4 weeks and found shorter STL and decreased telomerase expression in germ cells in a dose-dependent manner. In conclusion, environmental exposure to some PAHs may be associated with decreased human STL, and the in vivo animal results also demonstrate the adverse effects of B[ a ]P on telomere of male germ cells. Highlights: We measured eight urinary PAH metabolites as exposure markers. Associations of urinary PAH metabolites with semen quality, sperm apoptosis and STL were assessed in college students. Urinary 1-OHPyr and 1-OHNap were negatively associated with STL. No significant associations between urinary PAH metabolites and semen quality or sperm apoptosis were found. B[ a ]P shortened STL and decreased the telomerase expression in germ cells in vivo animal experiments.